Predictors of satisfaction with Kenya's police and Kenya's criminal justice system: Results from a sample of Kenyan college students. (December 2019) - Pryce, Daniel K; Wilson, George; Fuller, Kenethia
Although the influence of procedural justice on citizens' satisfaction and cooperation with police has been tested in several geopolitical contexts, this is the first study to examine the relationship between procedural justice and satisfaction with Kenya's police and Kenya's criminal justice system on a Kenyan college campus. Using a sample of 523 students from a prominent Kenyan university, we found that procedural justice and officer integrity predicted satisfaction with both Kenya's police and criminal justice system. Also, more highly educated students (sophomores, juniors, and seniors, compared to freshmen) were more satisfied with both the Kenyan police and criminal justice system. Conversely, victims of crime in the community were less satisfied with Kenyan police, and students who had a negative personal experience with police were less satisfied with the country's criminal justice system. Although instrumental factors of policing (e.g., police effectiveness) were not tested in this study, thus precluding a comparative assessment of normative and instrumental models of policing, this study contributes to the extant literature by pointing out the salience of procedural justice and officer integrity for improving the relationship between the police and the communities they are sworn to serve. The study's implications for policy are discussed.